Modelo de mudança organizacional: estudo de caso no setor de compras - FERNANDES, Lucas Athayde (Universidade Federal do Pará, 2014)
This paper presents a model of organizational change to improve the business process purchases from the communication system between the Central Office and works at construction company, to identify opportunities and deficiencies in the system is a technological and / or management. The mapping of information to detect unnecessary pathways that prevent communication system operating in an agile and optimized as well as realize opportunities for continuous improvements to the process. The research method was based on the improvement of business processes, which consists in modeling the process mentioned, through data collection, analysis documents, design flow of information existing in the model and discussion of results. For validation of the method, it was the single case study in a construction of buildings subsector, which generated flowcharts purchasing process current and proposed as a model of organizational change.